HUBUNGAN PATIENT SAFETY DENGAN MUTU PELAYANAN DI RUANG RAWAT INAP RSUD DR. WAHIDIN SUDIRO HUSODO KOTA MOJOKERTO - Dwi Helynarti Syurandhari (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2016)
Patient safety is part of quality and safety is a goal that most can be felt by the patient. Quality services certainly will not injure the patient. Service quality is definitely safe. Instead, the service quality is not necessarily safe and error-free. The purpose of this research to determined the relationship of patient safety with the service quality inpatient hospital Dr wahidin sudiro husodo mojokerto. This research is an analytic correlation with cross sectional approach. The population in this study were all inpatient hospital Dr wahidin sudiro husodo mojokerto taken from the average number of patients in the first month that as many as 156 patients. Sampling technique using Proporsionate Stratified Random Sampling and obtained a sample of 61 respondents. The independent variables in this study is patient safety and and the dependent variable in this study is the quality of sevice. Data analysis using chi- square test. Statistically, there is a relationship of patient safety with quality of care in inpatient hospital Dr wahidin sudiro husodo mojokerto. with r value (0.008) <α (0.05). The importance of promoting a culture of patient safety as one of the main issues on hospital accreditation standards closely related to quality of care. In line with this important also improved the quality of service on tangible indicators (direct evidence), considering the quality of service on tangible indicators and empathy are still valued less by respondents